^{2}+17x-46=

3x^2+17x-46=

could have two answer I think

Tutors, sign in to answer this question.

3x^{2}+17x-46=

3x2-6x+23x-46=

3x(x-2)+23(x-2)=

(3x+23)(x-2)

Dear David,

3x^{2} + 17x - 46 = (x - 2)(3x + 23)

If the original expression is equal to 0, then the two solutions are x = 2 and x = -7 and two thirds.

James H. | Math Tutor and Educational ConsultantMath Tutor and Educational Consultant

I will presume that the expression is equal to zero.

Solve by factoring: 3x^{2} + 17x - 46 = 0

Factor: (3x + 23) (x - 2) = 0

Set equal to zero: 3x + 23 = 0 and x - 2 = 0

Solve: x = -23/3, 2

Note, check by plugging the two answers into the original equation. The -23/3 answer is a pain to check, but it did check out in the end. It's good advanced arithmatic practice!

Acutally the answer is x= 2, -7 2/3

-23/3 = -7 2/3, because twenty-three divided by three is seven with a remainder of 2. This is actually an important lesson. In calculus I would often have the correct answer, but it was written in a different form than the authors wrote it in the answer section in the back of the book. In any case, I'm just glad I was able to help.

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments